Pengaruh Penggunaan Pendekatan Pembelajaran Kelompok terhadap Hasil Belajar Akidah Akhlak Siswa - Hazmar, Al Afif; Marlian, Marlian (STAI Auliaurrasyidin Tembilahan, 2021)
This study aims to determine the difference between the learning outcomes of Akidah Akhlah using the Collaborative learning approach and the conventional learning approach at Madrasah Tsanawiyah Negeri Pekan Heran, West Rengat District, Riau of Indonesia. Experimental methods were used in this study, while data collection techniques used observation, tests, and documentation. The results showed that the use of the Collaborative learning approach was very good at 88.46%. The experimental class was also categorically very good by 85.48%, while the control class was categorically as good only by 78.39%. There was a significant difference between the learning outcomes using the Collaborative learning approach and the conventional one. This study illustrated that the t value is greater than the t table at a significant level of 5% or 2.5688 > 2,00030.